An approach to quantitate maternal transcripts localized in sea urchin egg cortex using RT-qPCR with accurate normalization. - Yulia O Kipryushina; Mariia A Maiorova; Konstantin V Yakovlev (PLoS ONE, 2022)
The sea urchin egg cortex is a peripheral region of eggs comprising a cell membrane and adjacent cytoplasm, which contains actin and tubulin cytoskeleton, cortical granules and some proteins required for early development. Method for isolation of cortices from sea urchin eggs and early embryos was developed in 1970s. Since then, this method has been reliable tool to study protein localization and cytoskeletal organization in cortex of unfertilized eggs and embryos during first cleavages. This study was aimed to estimate the reliability of RT-qPCR to analyze levels of maternal transcripts that are localized in egg cortex. Firstly, we selected seven potential reference genes, 28S, Cycb, Ebr1, GAPDH, Hmg1, Smtnl1 and Ubb, the transcripts of which are maternally deposited in sea urchin eggs. The candidate reference genes were ranked by five different algorithms (BestKeeper, CV, ΔCt, geNorm and NormFinder) based on calculated level of stability in both eggs as well as isolated cortices. Our results showed that gene ranking differs in total RNA and mRNA samples, though Ubb is most suitable reference gene in both cases. To validate feasibility of comparative analysis of eggs and isolated egg cortices, we selected Daglb-2 as a gene of interest, which transcripts are potentially localized in cortex according to transcriptome analysis, and observed increased level of Daglb-2 in egg cortices by RT-qPCR. This suggests that proposed RNA isolation method with subsequent quantitative RT-qPCR analysis can be used to determine cortical association of transcripts in sea urchin eggs.